2002
DOI: 10.1038/nn828
|View full text |Cite|
|
Sign up to set email alerts
|

Glial cells generate neurons: the role of the transcription factor Pax6

Abstract: Radial glial cells, ubiquitous throughout the developing CNS, guide radially migrating neurons and are the precursors of astrocytes. Recent evidence indicates that radial glial cells also generate neurons in the developing cerebral cortex. Here we investigated the role of the transcription factor Pax6 expressed in cortical radial glia. We showed that radial glial cells isolated from the cortex of Pax6 mutant mice have a reduced neurogenic potential, whereas the neurogenic potential of non-radial glial precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
612
2
9

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 698 publications
(671 citation statements)
references
References 48 publications
31
612
2
9
Order By: Relevance
“…Recently, it was demonstrated that Pax6 mutants have reduced neurogenesis. Retrovirally mediated Pax6 expression instruct radial glia cells to differentiate to neurons, indicating the dual role of radial glial cell, namely, contribution to neurogenesis in addition to the support of migrating neurons during development (Heins et al, 2002). Whether this pertains to adult cells is not clear.…”
Section: Stem Cells In the Cnsmentioning
confidence: 99%
“…Recently, it was demonstrated that Pax6 mutants have reduced neurogenesis. Retrovirally mediated Pax6 expression instruct radial glia cells to differentiate to neurons, indicating the dual role of radial glial cell, namely, contribution to neurogenesis in addition to the support of migrating neurons during development (Heins et al, 2002). Whether this pertains to adult cells is not clear.…”
Section: Stem Cells In the Cnsmentioning
confidence: 99%
“…Expression of several of these developmental signals has been shown in adult rodent SVZa precursors, including paired-box (Pax) 6 (Heins et al, 2002;Hack et al, 2004), empty spiracles-homeobox (Emx) 2 (Galli et al, 2002), distalless-homeobox (Dlx) 2 (Doetsch et al, 2002), sex determining region Y-box (Sox) 2 (Ferri et al, 2004;Komitova and Eriksson, 2004), and oligodendrocyte lineage gene (Olig) 2 (Hack et al, 2004). At present, however, little is known of transcription factor expression by progenitor cells in adult primate SVZa.…”
mentioning
confidence: 99%
“…toggle switch – (Fig. 1, blue box) that has been shown to determine cellular commitment and provides stability to transcriptional programs mediating binary cell fate choices 83, 84, 85, 86, 87. This has been observed in other cellular systems, such as the common myeloid progenitor (mutual inhibition of Gata1 and PU.1 ) 88 and embryonic stem cells (mutual inhibition of Oct4 and Cdx2 ) 89.…”
Section: Specific Gene Regulatory Network Circuits Regulate the Balanmentioning
confidence: 90%